Building Resilience through Territorial Planning: Water Management Infrastructure and Settlement Design in the Coastal Wetlands of Northern Apulia (Salpia vetus-Salapia) from the Hellenistic Period to Late Antiquity - Roberto Goffredo; Darian Marie Totten (Land)
This Gulf of Manfredonia has, for millennia, been the primary water feature of the coastal wetland of Northern Apulia, Italy, although modern reclamation works make writing its long-term history challenging. Our recent paleoenvironmental research has reconstructed the evolution of the southern half of this lagoon since the Neolithic period. Here, we write a history of water management and environmental change in this landscape from the perspective of two key urban sites: pre-Roman Salpia vetus and Roman Salapia. The Roman architectural historian Vitruvius recounts the abandonment of Salpia vetus and the refoundation of Salapia. We employ his narrative as a frame for a more complex environmental history, starting from a historiography of this landscape’s study and a summary of our interdisciplinary research agenda, which unifies environmental, topographical, remote sensing, and archaeological approaches. Resilience in this changeable wetland environment was only possible through an integrated and intentional management of water among rivers, the lagoon, and the Adriatic Sea. While Salpia vetus exploited this wetland and thrived for centuries, the settlement eventually collapsed due to human and environmentally impelled factors. Roman Salapia subsequently emerged with a different approach, new infrastructure, and a new location. This blueprint would sustain urban life in this wetland for six centuries and lay the groundwork for the Medieval town.